Alu‐mediated large deletion of the CDSN gene as a cause of peeling skin disease. (25th October 2013) - Wada, T.; Matsuda, Y.; Muraoka, M.; Toma, T.; Takehara, K.; Fujimoto, M.; Yachie, A.
<x xml:space="preserve">Abstract</x> Peeling skin disease (PSD) is an autosomal recessive skin disorder caused by mutations in CDSN and is characterized by superficial peeling of the upper epidermis. Corneodesmosin (CDSN) is a major component of corneodesmosomes that plays an important role in maintaining epidermis integrity. Herein, we report a patient with PSD caused by a novel homozygous large deletion in the 6p21.3 region encompassing the CDSN gene, which abrogates CDSN expression. Several genes including C6orf15, PSORS1C1, PSORS1C2, CCHCR1, and TCF19 were also deleted, however, the patient showed only clinical features typical of PSD. The deletion size was 59.1 kb. Analysis of the sequence surrounding the breakpoint showed that both telomeric and centromeric breakpoints existed within Alu‐S sequences that were oriented in opposite directions. These results suggest an Alu‐mediated recombination event as the mechanism underlying the deletion in our patient.